Learning improvement after PI3K activation correlates with de novo formation of functional small spines - Enríquez-Barreto, Lilian; Cuesto, German; Dominguez-Iturza, Nuria; Gavilan, Elena; Ruano, Diego; Sandi, Carmen; Ferrandez-Ruiz, Antonio; Martin-Vazquez, Gonzalo; Herreras, Oscar; Morales, Miguel (Frontiers in Molecular Neuroscience, 2014)
PI3K activation promotes the formation of synaptic contacts and dendritic spines, morphological features of glutamatergic synapses that are commonly known to be related to learning processes. In this report, we show that in vivo administration of a peptide that activates the PI3K signaling pathway increases spine density in the rat hippocampus and enhances the animals’ cognitive abilities, while in vivo electrophysiological recordings show that PI3K activation results in synaptic enhancement of Schaffer and stratum lacunosum moleculare inputs. Morphological characterization of the spines reveals that subjecting the animals to contextual fear-conditioning training per se promotes the formation of large spines, while PI3K activation reverts this effect and favors a general change towards small head areas. Studies using hippocampal neuronal cultures show that the PI3K spinogenic process is NMDA-dependent and activity-independent. In culture, PI3K activation was followed by mRNA upregulation of glutamate receptor subunits and of the immediate-early gene Arc. Time-lapse studies confirmed the ability of PI3K to induce the formation of small spines. Finally, we demonstrate that the spinogenic effect of PI3K can be induced in the presence of neurodegeneration, such as in the TG2576 Alzheimer’s mouse model. These findings highlight that the PI3K pathway is an important regulator of neuronal connectivity and stress the relationship between spine size and learning processes.